2023
DOI: 10.1002/jcp.30987
|View full text |Cite
|
Sign up to set email alerts
|

Gulp1 deficiency augments bone mass in male mice by affecting osteoclasts due to elevated 17β‐estradiol levels

Abstract: The engulfment adaptor phosphotyrosine‐binding domain containing 1 (GULP1) is an adaptor protein involved in the engulfment of apoptotic cells via phagocytosis. Gulp1 was first found to promote the phagocytosis of apoptotic cells by macrophages, and its role in various tissues, including neurons and ovaries, has been well studied. However, the expression and function of GULP1 in bone tissue are poorly understood. Consequently, to determine whether GULP1 plays a role in the regulation of bone remodeling in vitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…31,45 It has been observed that sex steroid deficiency, including lower testosterone and estrogen levels, has a significant influence on bone turnover especially osteoclasts and bone resorption, which is closely linked to the GULP1, Hif1α and CMKLR1 factors. 46–48 Additionally, it has been revealed that bone loss in orchiectomy rats was accompanied by increased RANKL, which could be counteracted by the RANKL inhibitor osteoprotegerin. 49 In this study, mice subjected to orchiectomy experienced severe bone loss 8 weeks after the surgery, which was mitigated by Rb2 treatment.…”
Section: Discussionmentioning
confidence: 99%
“…31,45 It has been observed that sex steroid deficiency, including lower testosterone and estrogen levels, has a significant influence on bone turnover especially osteoclasts and bone resorption, which is closely linked to the GULP1, Hif1α and CMKLR1 factors. 46–48 Additionally, it has been revealed that bone loss in orchiectomy rats was accompanied by increased RANKL, which could be counteracted by the RANKL inhibitor osteoprotegerin. 49 In this study, mice subjected to orchiectomy experienced severe bone loss 8 weeks after the surgery, which was mitigated by Rb2 treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Each organ was isolated from male wild-type or Gulp1 knockout mice at 8 weeks of age, lysed with Qiagen TissueLyser II, and reacted with TRIzol reagent to extract total RNA (Kim et al, 2023). Total RNA from 3T3-L1 cells was also extracted using TRIzol reagent.…”
Section: Rna Extraction Reverse Transcriptionpolymerase Chain Reactio...mentioning
confidence: 99%
“…Total RNA from 3T3-L1 cells was also extracted using TRIzol reagent. RT-PCR and qPCR were conducted as previously described (Kim et al, 2023). All primer sets used for both RT-PCR and qPCR are listed in Supporting Information S1: Table 2.…”
Section: Rna Extraction Reverse Transcriptionpolymerase Chain Reactio...mentioning
confidence: 99%